Electrooptical method for generating of optical vortices - Skab, I.; Vasylkiv, Yu.; Vlokh, R. (Видавництво Львівської політехніки, 2012)
We have shown that the conically shaped electric field created in electrooptic crystals can lead to appearance of orbital angular momentum in the outgoing light beam and generating of optical vortex. It is verified experimentally on Bi12GeO20 crystals.
Keywords: optical vortex; natural optical activity; Pockels effect